Optimalisasi Teknologi Komunikasi Digital untuk Pengembangan Pariwisata Telomoyo, Desa Pandean, Kecamatan Ngablak, Kabupaten Magelang - Nopriadi Nopriadi; Sintar Nababan (Lembaga Pengembangan Kinerja Dosen, 2024)
Indonesia is famous for tourism. Many tourist attractions in Indonesia are famous to foreign countries. Tourism is one of the fields that has great potential, especially to support the improvement of people's welfare. Magelang is one of the local and foreign tourist destinations. By the Indonesian government, Magelang is designated as one of the five super priority tourism areas in Indonesia. One of the most visited tourist attraction in Magelang is Telomoyo. Telomoyo is located in Pandean village, Ngablak sub-district, Magelang district, Central Java. Telomoyo itself is one of the destinations that offers natural beauty from a height. In addition, Telomoyo also features a variety of interesting tourist attractions. From the top of Telomoyo, visitors can see beautiful scenery, including Mount Merbabu, Mount Ungaran, and Lake Rawa Pening in the distance. However, the lack of utilisation of digital technology by tourism operators is a challenge in promoting the destination more widely. Therefore, this community service programme aims to improve communication skills and understanding of digital technology for Telomoyo tourism operators, in order to increase competitiveness and professionalism in the tourism industry. This PKM activity is expected to improve the skills of Telomoyo business actors in utilising and optimising digital communication technology both for management and for tourism promotion so that it has an impact on improving community welfare.